PsycEXTRA Dataset 2005
DOI: 10.1037/e468402008-001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the attrition process in volume crime investigations: Home Office research study 295

Abstract: The Home Office's purpose is to build a safe, just and tolerant society in which the rights and responsibilities of individuals, families and communities are properly balanced and the protection and security of the public are maintained. RDS includes staff within the Government Statistical Service (GSS). One of the GSS aims is to inform Parliament and the members of the public about the state of the nation and p rovide a window on the work and perf o rmance of government, allowing the impact of government poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 1 publication
2
25
0
Order By: Relevance
“…It was found that there was not sufficient data to build a model of detection for burglary other than dwelling in which the key measures were statistically significant; therefore, this model was abandoned. The bivariate analyses are available in Burrows et al (2005). 14.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there was not sufficient data to build a model of detection for burglary other than dwelling in which the key measures were statistically significant; therefore, this model was abandoned. The bivariate analyses are available in Burrows et al (2005). 14.…”
Section: Discussionmentioning
confidence: 99%
“…Selected incident characteristics make burglaries more solvable, predicting 67-92% (Greenberg et al, 1977), and 86% (Eck, 1979) of burglary case outcomes with 13% of cases screened in as having characteristics that justified investigation (Eck, 1979). On-scene capture and suspect identity information are characteristics most likely to result in arrest for residential burglaries (Greenwood, 1975;Eck, 1979;Eck, 1983;Coupe and Griffiths, 1996;Burrows et al, 2005;Paine & Ariel, 2013), non-residential burglaries (Coupe and Kaur, 2005;Burrows et al, 2005), robbery cases (Newiss, 2002) and theft from and of motor vehicles . For metal theft from railways, metal type, on-scene capture and scrap metal dealer visits were the strongest solvability factors (Robb, et al, 2014).…”
Section: Burglary 'Solvability'mentioning
confidence: 99%
“…Williams and J. Weetman Notes 1. Key UK studies and reports here include McCulloch (1996), Tilley and Ford (1996), McCulloch and Tilley (2000), Home Office (2001aOffice ( , 2001b, Morgan (2001), Burrows et al (2005a), Burrows et al (2005b), Prime and Hennelly (2003) and Williams (2004). 2.…”
mentioning
confidence: 95%